Een staatse strategie in een ’uitgestorven’ land. Organisatie en ten uitvoerlegging van de brandschat in Vlaanderen, 1585 tot 1604 - Kraker, A.M.J. de (BMGN - Low Countries Historical Review, 2006)
Adriaan M.J. de Kraker, A national strategy in an ‘extinct’ country. How looting was organized and carried out in Flanders from 1585 to 1604 Between 1585 and 1604 Flanders was systematically looted by the Estates General and Zeeland. To prevent this from happening, local inhabitants regularly paid a standard levy. The paper not only shows how looting was at its most successful (1593-1596) when it was organized along the lines of a military campaign penetrating deep into Flanders, but also how the income obtained from looting was administered and by whom. It goes onto give an insight into the motives of the stakeholders involved in the looting and the reactions of their victims. It shows clearly how and why the looting of Flanders came to an end. Finally, it calls upon similar research to be carried out in other parts of the Netherlands and argues for a better understanding of the social and economic impact of the looting that went on in Flanders.